Stationary Regimes and Transient in Two Systems with Limited Power Supply - Lebedenko, Ya.O.; Mikhlin, Yu.V. (Journal of Applied Nonlinear Dynamics, 2026)
Resonant behavior of two 3-DOF systems with a limited power supply (or so-called non-ideal systems) is analyzed. Resonant steady states are constructed by the multiple scales method. Transient is presented using the two-points Padé approximants containing exponents. Obtained analytical results are compared with a numerical simulation. It is shown that amplitudes of the resonance vibrations of the elastic sub-system can be essentially decreased by change of the system parameters.